PERENCANAAN RUANG TERBUKA HIJAU SEBAGAI AREA PENGEMBANGAN URBAN FARMING DARI GERAKAN EKONOMI MANDIRI (GEMI 0418) CIMAHI - Ekawati, June; Wijaya, Karto; Sofari, Herdi; Rahmat, Amat; Muchamad, Arief Nur; Suparyogi, Dudi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2025)
The development of urban farming on green open space land in the Cipageran Asri Housing neighborhood RT 04 RW 18 Cipageran Village, North Cimahi District, Cimahi City, West Java, is based on the problem of limited water supply, which causes green open space (RTH) to be neglected and dry up, as well as the need to support circular economic activities. The aim of community service activities in spatial planning from the PKM team is to plan green open spaces as an urban farming development area for the Independent Economic Movement (GEMI) 0418 Cimahi. The results obtained by the architectural team for the development of urban farming consisted of 3 zones, namely the open planting area zone in the south and terraces on the east edge, the greenhouse zone with verticulture in the middle, and the gazebo zone in the north part of the RTH. It is hoped that this green open space planning will attract more visits from people outside the region to learn about implementing a circular green economy and improve GEMI 0418 management and innovation performance.